1999
DOI: 10.1046/j.1365-2168.1999.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of a laparoscopically placed, adjustable gastric band in the treatment of morbid obesity

Abstract: The Lap-Band is an effective method for achieving good weight loss in the morbidly obese at up to 4 years of follow-up. Laparoscopic placement has been associated with a short length of stay and a low frequency of complications. The ability to adjust the setting of the device to achieve different degrees of gastric restriction has enabled progressive weight loss throughout the period of study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
0
12

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(156 citation statements)
references
References 17 publications
8
136
0
12
Order By: Relevance
“…Laparoscopic gastric banding has been shown to be safe and effective in the surgical treatment of morbid obesity [3,4]. Several experiences with different lengths of followup have confirmed that band positioning has lower mortality and complication rate as compared with other more invasive procedures [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic gastric banding has been shown to be safe and effective in the surgical treatment of morbid obesity [3,4]. Several experiences with different lengths of followup have confirmed that band positioning has lower mortality and complication rate as compared with other more invasive procedures [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Several experiences with different lengths of followup have confirmed that band positioning has lower mortality and complication rate as compared with other more invasive procedures [1][2][3][4]. Over the years, different technical variations have been proposed, all having different impacts on the technical improvement of band positioning and its results.…”
Section: Discussionmentioning
confidence: 99%
“…13 The ®nding of high homocysteine levels at the end of the second year when the rate of weight loss is usually low is important. This con®rms the need for continued nutritional monitoring and supplementation even when the rate of weight loss falls with time.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure creates an early sense of satiety after eating and has been shown to be safe and effective. 13 Patients with a body mass index (BMI) greater than 35 kgam 2 , suffering signi®cant medical, physical or psychosocial disabilities and who have attempted weight reduction by other means for at least 5 y are considered for entry into the Lap-Band program. Pre-operative assessment includes measurement of hemoglobin and red cell indices, iron studies, serum vitamin B 12 , serum folate, red-cell folate and fasting plasma total homocysteine.…”
Section: Study Subjectsmentioning
confidence: 99%
“…1 It is one of the most powerful medical interventions available. 2,3 It induces and maintains a substantial weight loss. 4 However, despite widespread use, there is only limited understanding of how the LAGB achieves this weight loss.…”
Section: Introductionmentioning
confidence: 99%